2014
DOI: 10.1007/978-3-319-11421-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Acceptance of Free-Floating Car Sharing Systems Using Smart Relocation Strategies: A Survey Based Study of car2go Hamburg

Abstract: Abstract. Rapid growth rates seem to indicate that recently introduced free-floating car sharing (FFCS) can mean a breakthrough for the car sharing idea. Like other vehicle sharing systems, FFCS systems face significant regional demand fluctuations. Thus, providers might have to reposition empty vehicles to not lose potential customers. However, this aspect has been hardly examined in research and practice. This study aims to investigate appropriate relocation strategies for this new type of car sharing system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Free-floating BSS constitute a more flexible and spontaneous category of vehicle-sharing: they allow hiring and returning a bicycle very close to the demand points, without being forced to pass by a station before or after the ride [21]. The reason for this revenue redistribution choice lies in the fact that FFBSS represent a sustainable alternative of transportation that helps in the global reduction of traffic and emissions in urban realities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Free-floating BSS constitute a more flexible and spontaneous category of vehicle-sharing: they allow hiring and returning a bicycle very close to the demand points, without being forced to pass by a station before or after the ride [21]. The reason for this revenue redistribution choice lies in the fact that FFBSS represent a sustainable alternative of transportation that helps in the global reduction of traffic and emissions in urban realities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the first two ideas might serve as an intuitive starting point, the third approach could lead to a deeper understanding of relocation requirements. It has been shown that the majority of car2go users is willing to walk up to 500 meters to start a ride with a car2go car [7]. This distance could serve as a diameter for demand areas within the operational area of FFCS systems.…”
Section: Ffcs Forecastingmentioning
confidence: 98%
“…This allows the operator to propose the user a change of his destination in return for a price reduction for his trip. Herrmann et al [7] conduct a survey among car2go users to derive potentially successful user-based relocation strategies.…”
Section: Relocation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations